Penerapan Spiritualitas Keugaharian Melalui Pembelajaran Sekolah Minggu - Udin Firman Hidayat (HUPERETES: Jurnal Teologi dan Pendidikan Kristen, 2023)
In this digital era, the digital generation is being confronted with the problem of the spread of a culture of consumerism and hedonism among young people. The culture of consumerism and hedonism leads to a feeling of dissatisfaction and greed. By using a qualitative research method with a literature study approach, the researcher proposes the application of the model of frugality spirituality in Sunday school learning to answer this problem. The results of this study indicate that the application of the frugality spirituality model can be carried out by adopting appropriate church policies, exemplary Sunday school teachers, teaching materials, and learning methods that are relevant to the spirit of being sufficient.Di era digital ini, generasi digital sedang diperhadapkan pada persoalan merebaknya budaya konsumerisme dan hedonisme di kalangan anak-anak muda. Budaya konsumerisme dan hedonisme bermuara pada sikap hati yang selalu merasa tidak puas dan keserakahan. Dengan menggunakan metode penelitian kualitatif dengan pendekatan study kepustakaan peneliti mengusulkan penerapan model spiritualitas keugaharian dalam pembelajaran Sekolah Minggu untuk menjawab persoalan ini. Hasil penelitian ini menunjukkan bahwa penerapan model spiritualitas keugaharian dapat dilakukan dengan pengambilan kebijakan gereja yang sesuai, keteladanan guru Sekolah Minggu, materi bahan ajar dan metode pembelajaran yang relevan bagi semangat berkecukupan.